Variation in Ribosomal DNA in the Genus Trifolium (Fabaceae) - Vozárová, Radka; Macková, Eliška; Vlk, David; Řepková, Jana (Plants (Basel, Switzerland), 2021)
The genus Trifolium L. is characterized by basic chromosome numbers 8, 7, 6, and 5. We conducted a genus-wide study of ribosomal DNA (rDNA) structure variability in diploids and polyploids to gain insight into evolutionary history. We used fluorescent in situ hybridization to newly investigate rDNA variation by number and position in 30 Trifolium species. Evolutionary history among species was examined using 85 available sequences of internal transcribed spacer 1 (ITS1) of 35S rDNA. In diploid species with ancestral basic chromosome number (x = 8), one pair of 5S and 26S rDNA in separate or adjacent positions on a pair of chromosomes was prevalent. Genomes of species with reduced basic chromosome numbers were characterized by increased number of signals determined on one pair of chromosomes or all chromosomes. Increased number of signals was observed also in diploids Trifolium alpestre and Trifolium microcephalum and in polyploids. Sequence alignment revealed ITS1 sequences with mostly single nucleotide polymorphisms, and ITS1 diversity was greater in diploids with reduced basic chromosome numbers compared to diploids with ancestral basic chromosome number (x = 8) and polyploids. Our results suggest the presence of one 5S rDNA site and one 26S rDNA site as an ancestral state.
Keywords: nucleotide polymorphism; 26S rDNA; genome structure; clover; fluorescent in situ hybridization; 5S rDNA